Comparison of Tissue Molecular Biomarker Testing Turnaround Times and Concordance Between Standard of Care and the Biocartis Idylla Platform in Patients With Colorectal Cancer. Issue 2 (11th June 2020) - Tsongalis, Gregory J; Al Turkmani, M Rabie; Suriawinata, Michael; Babcock, Michael J; Mitchell, Kristi; Ding, Yi; Scicchitano, Lisa; Tira, Adrian; Buckingham, Lela; Atkinson, Sara; Lax, Amy; Aisner, Dara L; et al.
Abstract: Objectives: Management of colorectal cancer warrants mutational analysis of KRAS/NRAS when considering anti–epidermal growth factor receptor therapy and BRAF testing for prognostic stratification. In this multicenter study, we compared a fully integrated, cartridge-based system to standard-of-care assays used by participating laboratories. Methods: Twenty laboratories enrolled 874 colorectal cancer cases between November 2017 and December 2018. Testing was performed on the Idylla automated system (Biocartis) using the KRAS and NRAS-BRAF cartridges (research use only) and results compared with in-house standard-of-care testing methods. Results: There were sufficient data on 780 cases to measure turnaround time compared with standard assays. In-house polymerase chain reaction (PCR) had an average testing turnaround time of 5.6 days, send-out PCR of 22.5 days, in-house Sanger sequencing of 14.7 days, send-out Sanger of 17.8 days, in-house next-generation sequencing (NGS) of 12.5 days, and send-out NGS of 20.0 days. Standard testing had an average turnaround time of 11 days. Idylla average time to results was 4.9 days with a range of 0.4 to 13.5 days. Conclusions: The described cartridge-based system offers rapid and reliable testing of clinically actionable mutation in colorectal cancer specimens directly from formalin-fixed, paraffin-embedded tissue sections. Its simplicity and ease of use compared with other molecular techniques make it suitable for routine clinical laboratory testing.